Eosinophil and neutrophil extracellular DNA traps in human allergic asthmatic airways - Dworski, Ryszard; Simon, Hans-Uwe; Hoskins, Aimee; Yousefi, Shida (Journal of allergy and clinical immunology, 2011)
Asthma is a heterogeneous inflammatory airway disorder that involves eosinophilic and noneosinophilic phenotypes. Unlike in healthy lungs, eosinophils are often present in atopic asthmatic airways, although a subpopulation of asthmatic subjects predominantly experience neutrophilic inflammation. Recently, it has been demonstrated that eosinophils and neutrophils generate bactericidal extracellular traps consisting of DNA and cytotoxic granule proteins. We sought to explore whether living eosinophils and neutrophils infiltrating human atopic asthmatic airways actively form extracellular DNA traps in vivo. Quantitative analysis of eosinophils releasing DNA was performed in endobronchial biopsy specimens from 20 human subjects with mild atopic asthma at baseline and after local allergen challenge and 10 healthy subjects. DNA was stained with propidium iodine and major basic protein with specific antibody. Differential cell counts and cytokines/chemokines were assessed in bronchoalveolar lavage fluid. Asthmatic airways were infiltrated with a significantly higher number of eosinophils than healthy airways (39.3 ± 4.6 vs 0.4 ± 0.9, P < .0001). All asthmatic subjects but only 1 control subject expressed eosinophils releasing DNA that colocalized with major basic protein (33.65 ± 20.33 vs 0.3 ± 0.9 per high-power field, P < .0001). Four asthmatic subjects mostly expressed neutrophilic inflammation and neutrophil DNA traps. Allergen challenge had no significant quantitative effect on eosinophil or neutrophil DNA traps. Airway eosinophils or DNA traps did not correlate with either bronchoalveolar lavage levels of IL-5, IFN-γ, or eotaxin or the provoking doses of methacholine or allergen in asthmatic subjects. Extracellular DNA traps are generated by eosinophils and neutrophils in human atopic asthmatic airways in vivo. The mechanism and role of this new finding will necessitate further investigation.